ANALISIS SISTEM PENGELOLAAN IDLE MONEY PADA PT BANK CENTRAL ASIA (BCA) KANTOR CABANG TANJUNG PURA PONTIANAK DALAM MENINGKATKAN PROFIT - B51112003, Mega Sinlyanthony (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Banks have an important role in the economy of the country as a financial intermediary. As an industry whose business activities rely on the trust of society, besides the need to continue to improve its profitability, the bank also needs to continue to maintain the liquidity of the fund as a form of accountability to customers. In the bank's cash flow activity, settles the money created is often called idle money. Idle money needs to be minimized without lowering the existence of liquidity of customer funds in order to create new profit through appropriate management, the way through the establishment and application of cash balances ideal. This study aims to assess the steps taken by management in order to minimize the amount of idle money in physical cash BCA. Besides reviewing the calculation to determine the maximum amount of idle money that is allowed in accordance with the SOP and how the money is managed to minimize idle existence is then used to create a profit for the BCA. Through interviews and direct observation by using questionnaires, and then analyzed by the Internal Control Questionnaire (ICQ) and Flow Chart. The results showed that pnentuan idle money BCA Branch of Tanjung Pura Pontianak in accordance with the standards of the company in the form of decree No: 180 / SK / DIR / 2004 of idle money and cash balances ideal and SE / SK regarding the implementation of applications Icom SE No. 067 / SE / DPO / 2008 dated June 6, 2008 regarding Cash Management Optimization with Applications ICOM. The application of the ideal of cash balances in accordance with the provisions of the monthly operating centers in Jakarta by the branch office will minimize the amount of idle money, so that the working capital bank in the form of customer deposits can generate more income through the Interbank Money Market and ATM funds. Keywords: Idle money, Ideal Cash Balance, Standard Operating Company